Ebo (Sacrifice) in Ifa Religious Tradition of the Yoruba, Southwestern Nigeria and Its Implications for Public Health - Olaleye, Samuel Kayode; Gbadamosi, Oluwatoyin Adebola; Adekoya, Julius Sunday (Utan Kayu Publishing, 2025)
Ebo (sacrifice) is the feeding of spiritual entities such as gods, witches, and other energies believed to maintain equilibrium between the physical and spiritual worlds. It is an integral part of the Ifa divination system, a religious tradition in Yoruba society, southwestern Nigeria, which provides solutions to various problems. The materials for Ebo range from food items and animals to mineral and natural resources, including both living and nonliving things. Depending on the dictates of the Ifa oracle, Ebo can be offered at any time and placed in locations ranging from private spaces to public areas such as roadsides, rivers, gutters, or canals. Public reaction to the indiscriminate placement of Ebo is predominantly negative, except among practitioners or those offering it. This negativity stems from exposure to western education, foreign religions, and modern civilization. Common societal concerns include whether Ebo, beyond being an eyesore, contributes to air, water, and soil pollution, thus endangering public health. This paper aims to address the public health implications of Ebo placement. To explore these issues, interviews were conducted with 10 Babala?wo-Ifa priests, 10 men, and 10 women in Ibadan who had participated in offering Ebo. The content analysis of their responses revealed no consensus. Opponents of Ebo offerings cited speculative dangers, religious sentiments, and western education as factors shaping their views. This study highlights the complex interplay between traditional practices, modernity, and public health concerns, calling for further dialogue and solutions to mitigate potential risks.